Cancer and mTOR inhibitors in kidney transplantation recipients - Chih-Chin Kao (PeerJ, 2018)
Background Previous studies show that mTOR inhibitors decrease the risk of cancer development after kidney transplantation. However, the effect of cumulative doses of mTOR inhibitors on cancer after kidney transplantation is not well known. Methods In the current study, patients were registered into a national database in Taiwan. Between year 2000 and 2013, 4,563 patients received kidney transplantation. They were divided into two groups, according to mTOR inhibitors usage. The cumulative dose of mTOR inhibitors was recorded. Patients were followed-up until de novo cancer development, death, or the end of 2014. Results Patients were divided into two groups: mTOR inhibitors users (study group, n = 828) and mTOR inhibitors non-users (control group, n = 3,735). The median follow-up duration was 7.8 years. The risk of de novo cancer (hazards ratio (HR) 0.80, 95% CI [0.60–1.09], p = 0.16) and risk of death (HR 1.14, 95% CI [0.82–1.60], p = 0.43) was not different between mTOR inhibitor user and non-user groups. Neither high- nor low-dose exposure to mTOR inhibitors was associated with increased risk of cancer or mortality. Analysis of cancer subtypes showed no influence by mTOR inhibitors. In addition, the cause of mortality was not significantly different between the two groups. Discussion We could not find the association of mTOR inhibitors use and risk of de novo cancer development or mortality in patients with kidney transplantation in Chinese patients. Cumulative exposure to mTOR inhibitors did not change the results.